ON THE STRESSES IN AN ELASTIC PLASTIC ANNULAR DISK OF VARIABLE THICKNESS UNDER EXTERNAL-PRESSURE - GUVEN, U (PERGAMON-ELSEVIER SCIENCE LTD, 1993)
The plane state of stress in an elastic plastic annular disk of variable thickness subjected to external pressure is studied. The thickness of the annular disk is assumed to vary exponentially with any power of the radius. The analysis is based on Tresca's yield condition, its associated flow rule and linear strain hardening. The stresses are obtained in terms of confluent hypergeometric functions.
Keywords: Mechanics